Enhancing listening skills: issues and possible solutions - Aida, Gjinali; Eliona, Naqo (International Journal of Evaluation and Research in Education (IJERE), 2025)
The paper aims to investigate the extent to which listening skills development is realized in Italian language classes in Albanian pre-university education as one of the basic skills naturally interconnected comprehension and production. The research at hand is the first of this nature conducted in Albanian schools. The issues encountered in the development of this skill have been verified in our teaching experience; It has been noticed that students enrolled in the first-year encounter difficulties related to listening skills. Therefore, this study was considered as important and the relevant questionnaires were compiled. Following the collection of information, its analysis, and interpretation, possible suggestions were sought considering the encountered issues. The study revealed that this skill is underutilized or not utilized properly, as it is often not considered as a required skill. Students are limited to reading or listening skills only, delivered either by the teachers in class or through the few exercises provided by the foreign language book, without employing various strategies or techniques for its development and without using relevant authentic materials.